2018
DOI: 10.3390/s18092872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Thickness on the Sensitivity of Crack-Based Sensors

Abstract: Among many attempts to make a decent human motion detector in various engineering fields, a mechanical crack-based sensor that deliberately generates and uses nano-scale cracks on a metal deposited thin film is gaining attention for its high sensitivity. While the metal layer of the sensor must be responsible for its high performance, its effects have not received much academic interest. In this paper, we studied the relationship between the thickness of the metal layer and the characteristics of the sensor by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…When the two layers are tightly bonded together, the crack on one side can propagate to the other. The method of adding multi-layer materials is a new way to solve the problem of low adhesion [79] ; (b) schematic diagram of CBS for multiple interlayers [80] ; (c) schematic diagram of the fabricating steps and composition of PMSCSS [84] ; (d) upper left: When compressive strain F is applied, adjacent fracture surfaces reconnect and overlap, allowing electric current to pass through the connection area. Bottom left: Schematic representation of the relaxed and stimulated state.…”
Section: Polyethylene Terephthalate Based Crack Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…When the two layers are tightly bonded together, the crack on one side can propagate to the other. The method of adding multi-layer materials is a new way to solve the problem of low adhesion [79] ; (b) schematic diagram of CBS for multiple interlayers [80] ; (c) schematic diagram of the fabricating steps and composition of PMSCSS [84] ; (d) upper left: When compressive strain F is applied, adjacent fracture surfaces reconnect and overlap, allowing electric current to pass through the connection area. Bottom left: Schematic representation of the relaxed and stimulated state.…”
Section: Polyethylene Terephthalate Based Crack Sensormentioning
confidence: 99%
“…Lee et al reported CBS by depositing a few nanometers of chromium (Cr) and gold (Au) on a PET film ( Fig. 7b) [80] . In addition, the relationship between the thickness of the metal layer and the characteristics of the sensor was also investigated.…”
Section: Polyethylene Terephthalate Based Crack Sensormentioning
confidence: 99%
“…Typical highsensitivity sensors in the field of microelectromechanical system (MEMS) include silicon nanowires (SiNWs), graphene or carbon nanotube (CNT) composites, crack sensors, etc. [10][11][12][13][14][15][16][17][18][19][20][21]. Koumela et al…”
Section: Introductionmentioning
confidence: 99%
“…We used a 7.5 µm thick PI film (3022-5 Kapton thin film, Chemplex, Palm City, FL, USA) as a substrate of the crack-based sensor. According to a previous study, the depth and density of cracks are important factors that determine the sensor's sensitivity, and the thickness of the chromium is closely related to the depth of cracks [37,38]. Sensors have high sensitivity when the chromium layer is 60 nm thick and the gold layer is 20 nm thick, due to deep cracks and the low crack density effect (performance degradation due to a small number of cracks).…”
Section: Fabricationmentioning
confidence: 99%